A territorialidade camponesa no assentamento Sul Bonito em Itaquiraí - MS - Silva, Dherwerson dos Santos (2016)
Geography as a science has brought with it new thinking about man and nature; as well as various forms of man territorialize space to the maintenance of the process of life, but also to the reproduction of capitalist relations of production. In this context, the area appears as a representation of power to the identification of the subject so that it produces a territorial. This capitalist reproduction led to a rethinking of lower social classes, like the peasants, who were discriminated against by the dominant classes. This exploratory practice has been and continues to the present day, taking place in the country. Geography is a way of reading the world, to that end, we seek to understand the peasant world and its specifications, in this sense, the recent expansion of capitalist relations in the field led to the expropriation of the means of production of small farmers, among which the earth. This fact has caused many farmers from traveling to the cities. With this process of dispossession, it was up to the social movements the task of organizing this dispossessed population of territory in order to promote agrarian reform in Mato Grosso do Sul. The achievement of a settlement of territory led families to pay special attention to the organization production of family-based livelihoods, organization of cooperatives, collectives, etc. In South Beautiful settlement in Itaquiraí / MS, the aim of this study is to highlight the peasant territoriality and its mixed farming economy as part of strategies of resistance. In this context, this research is relevant to present a way of life that even inserted into a capitalized economy, has typically rural characteristics, which shows an alternative way of life that is contrary to the subordination of the capital